Magnetization and Specific Absorption Rate Studies of Ball-Milled Iron Oxide Nanoparticles for Biomedicine. (28th September 2013) - Burnham, P.; Dollahon, N.; Li, C. H.; Viescas, A. J.; Papaefthymiou, G. C.
Abstract : Comparative studies are presented of iron oxide nanoparticles in the 7–15 nm average diameter range ball milled in hexane in the presence of oleic acid. Transmission electron microscopy identified spherical particles of decreasing size as milling time and/or surfactant concentration increased. Micromagnetic characterization via Mössbauer spectroscopy at room temperature yielded broadened magnetic spectroscopic signatures, while macromagnetic characterization via vibrating sample magnetometry of 7-8 nm diameter particles showed largely superparamagnetic behavior at room temperature and hysteretic at 2 K. Zero-field and field-cooled magnetization curves exhibited a broad maximum at 215 K indicating the presence of strong interparticle magnetic interactions. The specific absorption rates of ferrofluids based on these nanoparticle preparations were measured in order to test their efficacies as hyperthermia agents.